Modified Relative Dose Response (MRDR) Survey - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
In this video, Fisayo Ogah, the South-West Zonal Coordinator for the survey explains that there are so many micronutrients, but vitamin A is very essential for good vision, a healthy immune system, and cell growth.